Uveal Melanoma and its Various Presentations – A Series of Case Reports - Sujit Das (TNOA Journal of Ophthalmic Science and Research)
Ocular melanoma is usually a secondary cancer and very rare. Ocular melanoma typically does not cause early signs or symptoms and hence is difficult to detect. About 12% of uveal melanoma arises from the ciliary body. Choroidal melanoma is the most common primary intra-ocular malignant tumour and the second most common metastatic site. Complications are glaucoma, vision loss, and metastasis to liver, lungs, and bones. Fine needle aspiration cytology can have significant morbidity and should only be considered if therapeutic intervention is indicated and diagnosis cannot be established by any other means.